2004
DOI: 10.1088/0953-4075/37/5/013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of single and double ionization of helium by ion impact

Abstract: We present three-dimensional angular distributions of the sum momentum vector of electrons emitted in double ionization in 6 MeV p + He collisions for fully determined kinematics. The results are directly compared to corresponding data for single ionization. Qualitative similarities between single and double ionization are observed. However, we demonstrate that based on these similarities it cannot be concluded that the collision dynamics underlying both processes are similar as well.Furthermore, we find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…[2] proved the existence of the node. This is a remarkable result, because previous experiments [3][4][5] did not show the node in strong disagreement even with the most advanced theories. Although the failure of the latter experiments to observe the node most likely was due to the insufficient momentum resolution, other instrumental effects cannot be ruled out.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…[2] proved the existence of the node. This is a remarkable result, because previous experiments [3][4][5] did not show the node in strong disagreement even with the most advanced theories. Although the failure of the latter experiments to observe the node most likely was due to the insufficient momentum resolution, other instrumental effects cannot be ruled out.…”
Section: Introductionmentioning
confidence: 56%
“…Silverman-Platas-Matsen (SPM) [34] wave functionThe position distribution:ρ SPM (r) = 1 (1 + λ 2 ) N 2 R 2 10 (r) + R 2 10 (r) + 2R 10 (r)R 10 (r)S + λ 2 R 2 21 (r) r 2 , (A7) with R 10 (r) = 2a 3/2 exp(−ar), R 10 (r) = 2b 3/2 exp(−br), R 21 (r) = (2/ √ 3)g 5/2 r exp(−gr), 10 (r)R 10 r 2 dr = 8(ab) 3/2 /(a + b) 3 , N = (2 + S 2 ) −1/Here λ = −0.0617557, a = 2.17621, b = 1.20152, and g = 2.47547. The fit of the integral (5) to ρ SPM (r) was made with the GSZ potential[27] in Eq (4)…”
mentioning
confidence: 99%
“…In the plane perpendicular to the momentum transfer the expected node was filled and theory and experiment showed severe disagreement. While even the most advanced theories to date still predict a node [7][8][9][10], further experiments showed a similar behavior of a (partly) filled node [11][12][13]. The authors of [10,14] suggested, that the origin of the discrepancies observed in Schulz' experiment is a result of insufficient momentum resolution, which however was refuted by Schulz et al [15].…”
mentioning
confidence: 99%
“…One might expect that the dynamics of these reactions differs significantly from one-electron transitions, such as SI, because of the increased importance of electron-electron correlations [22] and because a larger final-state phase space is available for two active electrons. Nevertheless, amazing similarities between DI and SI were obtained in so far as the characteristic binary/recoil double lobe structure, well known from SI studies, was observed in the three-dimensional angular distribution of the sum momentum of both electrons ejected in double ionization [23].…”
Section: 7]mentioning
confidence: 66%